Recent progress in L–H transition studies at JET: tritium, helium, hydrogen and deuterium. (1st July 2022) - Solano, E.R.; Delabie, E.; Birkenmeier, G.; Silva, C.; Hillesheim, J.C.; Vincenzi, P.; Nielsen, A.H.; Rasmussen, J.Juul; Baciero, A.; Aleiferis, S.; Balboa, I.; Boboc, A.; et al.
Abstract: We present an overview of results from a series of L–H transition experiments undertaken at JET since the installation of the ITER-like-wall (JET-ILW), with beryllium wall tiles and a tungsten divertor. Tritium, helium and deuterium plasmas have been investigated. Initial results in tritium show ohmic L–H transitions at low density and the power threshold for the L–H transition ( P LH ) is lower in tritium plasmas than in deuterium ones at low densities, while we still lack contrasted data to provide a scaling at high densities. In helium plasmas there is a notable shift of the density at which the power threshold is minimum ( n ¯ e, min ) to higher values relative to deuterium and hydrogen references. Above n ¯ e, min (He) the L–H power threshold at high densities is similar for D and He plasmas. Transport modelling in slab geometry shows that in helium neoclassical transport competes with interchange-driven transport, unlike in hydrogen isotopes. Measurements of the radial electric field in deuterium plasmas show that E r shear is not a good indicator of proximity to the L–H transition. Transport analysis of ion heat flux in deuterium plasmas show a non-linearity as density is decreased below n ¯ e, min . Lastly, a regression of the JET-ILW deuterium data is compared to the 2008 ITPA scaling law.